ANALISIS SALDO PRIMER POSITIF PADA TAHUN 2023 SEBAGAI INDIKATOR APBN PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN - Fahrudin, Moch (MAGISTRA Law Review, 2024)
The 2023 State Revenue and Expenditure Budget (APBN) shows a positive figure of 92.2 trillion. This has been anticipated since 2012, and it has always been in a negative condition. This is an indicator of the improving health of the APBN, as a manifestation that leads to better economic conditions and the welfare of Indonesian society in general. The primary balance is state income minus state expenditure without debt interest payments. In determining the initial assumptions of the 2023 APBN Law, the primary balance is in negative condition. And, until the end of 2023, it shows a positive balance how This condition can show that the economy is developing with greater income, which will impact people's welfare.